2008
DOI: 10.1093/ajcn/87.5.1428
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acrylamide intake and the risk of renal cell, bladder, and prostate cancer

Abstract: We found some indications for a positive association between dietary acrylamide and renal cell cancer risk. There were no positive associations with bladder and prostate cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 44 publications
10
102
3
1
Order By: Relevance
“…In a study, the relationship between acrylamide intake in humans depending on the diet and kidney cancer, it was revealed that the kidney function was affected and there was a positive relationship between acrylamide and increase in kidney-cell cancer [44]. Moreover, it was also determined that there was a positive relationship between kidney cancer formation in humans as well as animals and oestrogen hormone [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the relationship between acrylamide intake in humans depending on the diet and kidney cancer, it was revealed that the kidney function was affected and there was a positive relationship between acrylamide and increase in kidney-cell cancer [44]. Moreover, it was also determined that there was a positive relationship between kidney cancer formation in humans as well as animals and oestrogen hormone [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation, the obtained upper hexane layer was discarded. The remaining solution was mixed with ISOLUTE® (Biotage AB, Uppsala, Sweden), PSA, C18EC (a retentive, non-polar sorbent for extraction of a range of analytes from aqueous samples) and MgSO 4 , and then centrifuged at 755×g for 5 min. A volume of 1000 µL of the extracted solution was transferred into HPLC autosampler vial for acrylamide estimation (16,17).…”
Section: Extraction Of Acrylamide From Fried Kochchi Kesel Chipsmentioning
confidence: 99%
“…The investigation on human neurotoxicity to acrylamide exposure showed that the activity of glutathione S-transferase (GST) in brain was inhibited with the increase in brain dopamine concentration. It was reported that acrylamide was well absorbed and distributed widely in tissues on oral administration (4). Food researchers around the world are in the process of establishing a valid strategy for the mitigation of acrylamide concentration in fried foods.…”
Section: Introductionmentioning
confidence: 99%
“…ACR also crosses placenta to developing fetus significantly, leading to direct prenatal and postnatal anomalies (10). ACR is existent in foods at extremely higher condensation up to other popular food carcinogens (11). ACR quickly metabolizes in body and its metabolites are mostly excreted through the urine (12).…”
Section: Introductionmentioning
confidence: 99%